2004
DOI: 10.1037/0893-3200.18.4.589
|View full text |Cite
|
Sign up to set email alerts
|

The Interpersonal Process Model of Intimacy: The Role of Self-Disclosure, Partner Disclosure, and Partner Responsiveness in Interactions Between Breast Cancer Patients and Their Partners.

Abstract: This study evaluated H. Reis and P. Shaver's (1988) interpersonal process model of intimacy in a sample of 98 women with breast cancer and their partners. Couples engaged in two discussions and rated self- and partner disclosure, perceived partner responsiveness, and intimacy experienced. A mediational model was tested in which partner responsiveness mediated the association between disclosure and intimacy. For patients, perceived responsiveness partially mediated the association between partner disclosure and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
177
6
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 210 publications
(198 citation statements)
references
References 33 publications
8
177
6
3
Order By: Relevance
“…Couples participated in 2 discussions and then rated perceived self-disclosure, partner disclosure, partner responsiveness, and intimacy experienced during the discussion. 119 When the partner's perspective was evaluated, our findings were consistent with the interpersonal process model of intimacy. However, when the patient's perspective was evaluated, the findings were only partially supportive of the Interpersonal Process Model.…”
Section: Dyadic Level Theoriessupporting
confidence: 71%
See 2 more Smart Citations
“…Couples participated in 2 discussions and then rated perceived self-disclosure, partner disclosure, partner responsiveness, and intimacy experienced during the discussion. 119 When the partner's perspective was evaluated, our findings were consistent with the interpersonal process model of intimacy. However, when the patient's perspective was evaluated, the findings were only partially supportive of the Interpersonal Process Model.…”
Section: Dyadic Level Theoriessupporting
confidence: 71%
“…Although these findings suggest that patient self-disclosure may not play a strong role in relationship closeness, our observational work suggests that partners' responses-particularly partner's reciprocal self-disclosures-play a role in patients' distress. 119 Behavioral marital theory. We include behavioral marital theory because it is a hallmark of the vast majority of couple-focused interventions in the marital literature and has guided some of our recent approaches to understanding relationship processes in cancer.…”
Section: Dyadic Level Theoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, as we learn more about a person, we tend to rely more on that new information and less on stereotypes. Similarly, disclosure research has shown that sharing personal information with others can foster intimacy, liking, and trust (Collins & Miller, 1994;Manne et al, 2004;Turner, Hewstone, & Voci, 2007). Therefore, because relationships are constantly changing over time as people have new experiences with and learn more about each other, examining the extent to which an individual perceives, witnesses, or engages in subtle discrimination with a particular person at a single snapshot in time is insufficient to fully understanding the experience and consequences of subtle discrimination within a particular relationship.…”
Section: The Dynamic Nature Of Relationshipsmentioning
confidence: 99%
“…Por tanto, estos resultados podrán contribuir a desmitificar la creencia de que el diagnóstico y la vivencia del cáncer de mama aportan a la disminución de la satisfacción en la relación de pareja. Si se tiene en cuenta que la sexualidad es un dominio importante en la vida íntima de la pareja, la cual representa uno de los ingredientes principales en una relación interpersonal próxima se entiende que un buen nivel de satisfacción en esta área puede contribuir a aumentar el nivel de satisfacción marital en general (108) . Así, estos resultados pueden servir para empoderar las parejas que están atravesando una condición de enfermedad similar, en el sentido en que brinda algún entendimiento sobre la posibilidad de acercamiento que la experiencia de cáncer puede llegar a tener en la relación.…”
Section: Discussionunclassified